Toward next JENDL Fission Yield Data and Decay Data - Minato Futoshi (EPJ Web of Conferences, 2020)
JENDL group has developed evaluated fission yield and decay data. They are now planned to be upgraded in order to embody new experimental data and theoretical developments obtained after the last release. In this paper, we briefly describe a plan and present activity toward next JENDL fission yield and decay data.